Microbes Against Humanity, a workshop game for horrible students: using a creative card game in higher education microbiology teaching. Issue 2 (3rd February 2021) - Efthimiou, Georgios; Tucker, Nicholas P.
Abstract : Introducing creative workshops in higher education curricula, in addition to formal lectures, is an excellent way of reinforcing knowledge and encouraging creative thinking. In particular, the use of card games as a tool for inducing student engagement and enthusiasm has been reported to be a very effective approach. Here, we report an innovative card game-based workshop for use at the intermediate undergraduate level. The name of the game is Microbes Against Humanity and has been adapted from the widely known party game Cards Against Humanity, which is freely available under a creative commons licence. Overall, 64 students and two academics participated in this 2 h workshop. Our students found the workshop to be very enjoyable, considered it to be helpful for their learning and suggested interesting ideas for further improvement. In conclusion, it was shown that such exciting workshops can trigger students' enthusiasm for microbiology and enhance their learning potential.